Characterization and management of adverse events observed with mobocertinib (TAK-788) treatment for EGFR exon 20 insertion–positive non–small cell lung cancer. Issue 1 (2nd January 2023) - Yang, James Chih-Hsin; Zhou, Caicun; Jänne, Pasi A.; Ramalingam, Suresh S.; Kim, Tae Min; Riely, Gregory J; Spira, Alexander I; Piotrowska, Zofia; Mekhail, Tarek; Garcia Campelo, Maria Rosario; Felip, Enriqueta; Bazhenova, Lyudmila; et al.
ABSTRACT: Background: Mobocertinib has demonstrated durable clinical benefit in platinum-pretreated patients (PPP) with epidermal growth factor receptor exon 20 insertion–positive non–small cell lung cancer (NSCLC). Research design and methods: Pooled safety analysis of two studies included patients with NSCLC (N = 257) treated with the recommended phase 2 dose (RP2D) of mobocertinib (160 mg once daily). We report overall safety (treatment-emergent adverse events [TEAEs]) in the RP2D population; characterization of GI and skin-related events in 114 PPP from a phase 1/2 study (NCT02716116); and clinical activity in PPP with and without dose reductions due to TEAEs. Results: In the RP2D population (N = 257), the most common TEAEs were diarrhea (93%), nausea (47%), rash (38%), and vomiting (37%). In PPP (N = 114), median times to diarrhea onset and resolution were 5 and 2 days, respectively. Median times to onset and resolution of skin-related events were 9 and 78 days, respectively. Among PPP with (n = 29) or without (n = 85) dose reductions due to TEAEs, overall response rates were 21% and 31% and median durations of response were 5.7 and 17.5 months, respectively. Conclusions: GI and skin-related events are common with mobocertinib; minimizing dose reductions with proactive management may improve clinical outcomes. Trial Registration: NCT02716116; NCT03807778 Plain Language Summary: Mobocertinib is a treatment for patients with a certain type of lung cancer. We analyzed the safety of mobocertinib in 257 patients with lung cancer. The most common side effects with mobocertinib were diarrhea, nausea, vomiting, and skin rash. In 114 patients with lung cancer who were treated in the past with chemotherapy that included platinum-based drugs, diarrhea started after about 5 days of mobocertinib treatment and went away in about 2 days. Skin-related side effects started after about 9 days and went away in about 2.5 months. One-fifth of patients who had to receive a smaller amount of mobocertinib because of side effects responded to treatment compared with one-third of patients who received the recommended mobocertinib amount. Managing side effects quickly can better help patients with lung cancer who are treated with mobocertinib.